EFFECT OF FIBER LENGTH ON MECHANICAL PROPERTIES OF PALF REINFORCED BISPHENOL: A COMPOSITE - MR. P. C. DAGADE; PROF. S. M. SHAIKH (International Journal of Innovations in Engineering Research and Technology, 2021)
Composites are becoming an essential part of today’s materials because they offer advantages such as low weight, corrosion resistance, high fatigue strength, faster assembly etc. Composites are used as materials ranging from making, aircraft structures to golf clubs, electronic packaging to medical equipments. Composites are generating curiosity and interest in students all over the world, use of natural fibers as reinforcement in polymeric composites for technical application has been a research subject of scientist. Among several natural fibers, Pineapple leaf fibre (PALF) is one that has good potential as reinforcement in polymer composite.